(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Background: Pleural effusions are suspected by physical examination and suggested by X-ray chest. Pleural aspiration is considered next to x-ray chest. If fluid is aspirated, it is dealt according to the guide-line. If no fluid is found, then next possibility is considered. Chest ultrasound has appeared as an invaluable modality for the assessment and management of pleuro-pulmonary disorders. Objectives: To evaluate the usefulness of trans-thoracic ultrasonography for diagnosis and planning the management of pleuro-pulmonary disorders. Patients and methods: This retrospective study included 3831 consecutive cases, scanned at OPD of Gulab Devi Chest Hospital, Lahore from October 2016 till February 2018. The undiagnosed cases suggestive of having pleural effusion on chest x-ray (CXR) were included. The records of the patients were retrieved, ultrasonographic findings and final diagnosis were recorded. Results were tabulated and statistical analysis was performed using SPSS 16. Categorical data was presented as percentage and quantitative data was expressed as mean with standard deviation. Results: Pleural effusions were found in 2058/3831 (53.71%) cases; 915 (23.88%) with normal pleurae, 27 (0.70%) collapse, 303 (7.90%) consolidation, 366 (9.55%) pleural thickening, 87 (2.27%) pleuro-phrenic adhesions and the diagnosis of mass lesion was made in 27 (0.7%) patients. It eliminated the need of pleural aspiration in 1773 (46.28%) cases by ruling out pleural effusion in which attempted pleural aspiration and organ puncture was inevitable otherwise. Conclusion: Trans-thoracic ultrasound is extremely useful for diagnosing and planning management for suggested pleuro-pulmonary disorders.